PLK-1 Regulation of Asymmetric Cell Division in the Early C. elegans Embryo - Kim, Amelia J.; Griffin, Erik E. (Frontiers in Cell and Developmental Biology, 2021)
PLK1 is a conserved mitotic kinase that is essential for the entry into and progression through mitosis. In addition to its canonical mitotic functions, recent studies have characterized a critical role for PLK-1 in regulating the polarization and asymmetric division of the one-cell C. elegans embryo. Prior to cell division, PLK-1 regulates both the polarization of the PAR proteins at the cell cortex and the segregation of cell fate determinants in the cytoplasm. Following cell division, PLK-1 is preferentially inherited to one daughter cell where it acts to regulate the timing of centrosome separation and cell division. PLK1 also regulates cell polarity in asymmetrically dividing Drosophila neuroblasts and during mammalian planar cell polarity, suggesting it may act broadly to connect cell polarity and cell cycle mechanisms.